Headache in diabetes - Sanjay Kalra; Suneet Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
Diabetes can present with multiple manifestations and subjective symptoms. One of these is headache. Headache can be a clinical presentation of diabetes per se, its complications or its comorbidities. It can also point towards certain causes of secondary diabetes, as well as iatrogenic issues. This communication lists the various causes of headache in diabetes, so as to help the clinician keep a high index of vigilance. Keywords: Adverse drug reactions, hyperglycaemia, hypoglycaemia, neurology, ophthalmology, psychiatry, psychology.